REASSERTING THE ROLE OF ASBAB AL-NUZUL IN CONTEXTUALIZING QURANIC TEACHINGS: A CRITICAL HERMENEUTICAL INQUIRY IN THE MODERN AGE - Fatihatun Nadliroh; Suwarno; Ahmad Yusam Thobroni (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
This article explores the epistemological significance of asbab al-nuzul (occasions of revelation) as a hermeneutical tool for contextualizing Quranic teachings in the face of contemporary interpretive challenges. While traditionally regarded as historical annotations, asbab al-nuzul provide more than background context—they serve as critical frameworks that anchor the meaning of verses to their original socio-historical settings, thus preventing misreadings in modern applications. Employing a qualitative-descriptive method within a library research framework, this study critically engages with both classical and contemporary exegetical works. The findings reveal that integrating asbab al-nuzul into modern Quranic interpretation enhances both textual fidelity and contextual relevance, especially in navigating legal, ethical, and socio-political verses. In an era marked by pluralism, shifting norms, and the reconfiguration of Islamic thought, reaffirming the role of asbab al-nuzul becomes essential for maintaining the coherence, depth, and transformative potential of the Quranic message. This study advocates for a renewed hermeneutical approach that positions asbab al-nuzul not merely as ancillary data, but as a core interpretive mechanism in contemporary Quranic studies.